The impact of frailty index on long-term outcome in CRT patients. (3rd October 2022) - Kuthi, L; Schwertner, W; Veres, B; Merkel, E; Behon, A; Masszi, R; Kovacs, A; Osztheimer, I; Molnar, L; Zima, E; Geller, L; Kosztin, A; et al.
Abstract: Background: Frailty is a complex clinical syndrome associated with ageing and comorbidities resulting from multiple organ impairment by losing homeostatic reserves and increased vulnerability to physiological decompensation. Frailty can be measured by quantifying the "vulnerability status" by the range of comorbidities. Purpose: We assessed the long-term all-cause mortality based on Frailty Index (FI) among patients who underwent Cardiac Resynchronization Therapy (CRT) implantation. Methods: We calculated patients' FI individually using 30 clinical parameters from our retrospective single centre large-scale registry. The applied clinical features incorporated patients' medical history, anthropometric-, laboratory and echocardiographic parameters. Based on previous studies, patients with FI ≤0.210 were classified as non-frail, and patients above that value were considered frail. Frail patients were divided into two different subgroups (F1; F2) by a FI increment of 0.100 based on the Rockwood method. Primary endpoint was all-cause mortality, log-rank and Cox multivariate analysis were performed. Results: Among 1010 included patients, 58 (6%) were considered as Non-frail, while 245 (24%) and 707 (70%) participants were categorized to F1- and F2 groups. Patients in F2 group were older [non-frail 62 years (IQR 57–68) vs. F1 66 years (IQR 57–73) vs. F2 70 years (IQR 63–76); p<0.001], had worse laboratory parameters as higher creatinine, uric acid, lower sodium or hemoglobin levels (p<0.001) and more comorbidities than patients of Non-frail or F1 groups. During the median follow-up time of 4.4 (2.3–6.9) years, 17 (29%) patients in the Non-frail group, 103 (42%) in Frail group 1 and 479 (68%) in the Frail group 2 reached the primary endpoint. Non-frail patients showed the best outcome, and patients in the Frail group 1 demonstrated a 46% (HR 0.46, 95% CI 0.39–0.55; p<0.001) lower all-cause mortality risk compared to Frail group 2. In the total cohort, mortality predictors were also assessed, NYHA functional class, serum sodium, creatinine and TAPSE were identified as independent predictors of all-cause mortality. Conclusion: By calculating individual frailty index among CRT patients, distinct groups could be identified, of which mortality differed significantly. Those with the highest Frailty index demonstrated the worse outcome compared to lower index or non-frail patients. Frailty index can help selecting the most vulnerable patients, requiring a strict follow-up. Funding Acknowledgement: Type of funding sources: None.